PENGGUNAAN AKUNTANSI FORENSIK DALAM PENYELESAIAN KASUS KEPAILITAN - Nur Apandi, R. Nelly; Pradista, Yudha (Jurnal Riset Akuntansi dan Keuangan, 2014)
This research aim to know how bankrupt process and applying of forensic accountancy in bankrupt. Â Besides to know constraints any kind of faced in applying forensic accountancy in finishing case of bankrupt. This study uses qualitative methods. Informant this research consists of curators, civil servant, forensic accountants and Auditors.Result of this research indicate that forensic accountancy have role in assisting to finish case of bankrupt. This matter can be seen from some process or step is solving of case of done bankrupt in justice of commercial needing forensic accountancy. The first, checking off receivable and liability at litigation to prove that debtor really is having of debt to all creditor so that ascertain justice in deciding bankrupt an company. Second, enumeration of bankruptasset to data exist in document, financial statement, and debtor boldness with direct inspection in field. Third, checking off receivable and liability at the time of creditor meeting to know really conducted receivable and liability amount in agreement between creditor and debtor. Fourth, at the time of division of bankrupt asset to ascertain sequence of is division of between separatist creditor, preferential, and congruence seen the existence of guarantee or do not at the time of agreement of receivable and liability. Fifth, detecting the existence of indication of fraud that happened at case of bankrupt.